Exploring Innovative Work Behavior among Vocational Educators: A Qualitative Study in Private Vocational Schools in Indonesia - Reza Dwi Ramadhan; Umi Anugerah Izzati; Olievia Prabandini Mulyana (Journal of General Education and Humanities, 2026)
As the demands of the modern workforce evolve, the capacity of vocational educators to innovate becomes increasingly critical. However, research on innovative work behavior (IWB) has predominantly focused on public or general education settings, leaving a gap in understanding how IWB manifests in private vocational schools, which often face more acute resource constraints and market pressures. This study examines teachers’ IWB at a private vocational high school in East Surabaya, Indonesia. Employing a qualitative descriptive design, the study investigates how educators generate, promote, and implement innovative practices within the school context. Data were collected through semi-structured in-depth interviews with 12 participants, including school administrators and teachers across various vocational disciplines, and analyzed using Miles and Huberman’s interactive model. Findings reveal that while educators demonstrate robust IWB use, their innovation is specifically triggered by "survival-driven" adaptations to industrial demands and rigid curriculum dynamics. Notably, the role of leadership proved dualistic: acting as both a primary motivator through professional autonomy and a potential barrier through bureaucratic oversight. These results contribute to the literature by providing a contextualized model of IWB in private vocational education, underscoring that institutional support must move beyond administrative compliance to foster a collaborative climate that sustains long-term innovation.